The Training Stroke of Murray Rose - Rushall, B. S.
Video pictures (17 frames) and the appropriate technical/ biomechanical explanations for the training stroke of Murray Rose (freestyle long distance). This record was made by Forbes Carlile at the 1960 Olympic Games Swimming Team training camp in Queensland, Australia. Murray Rose has been mythologized as having had a "classic" stroke which has features worthy of emulation. It is popularly considered to be the forerunner of "modern" crawl-stroke technique as well as exhibiting several innovations.